Emerging roles of endoplasmic reticulum stress in the cellular plasticity of cancer cells - Wang, Hao; Mi, Kun (Frontiers in Oncology, 2023)
Cellular plasticity is a well-known dynamic feature of tumor cells that endows tumors with heterogeneity and therapeutic resistance and alters their invasion–metastasis progression, stemness, and drug sensitivity, thereby posing a major challenge to cancer therapy. It is becoming increasingly clear that endoplasmic reticulum (ER) stress is a hallmark of cancer. The dysregulated expression of ER stress sensors and the activation of downstream signaling pathways play a role in the regulation of tumor progression and cellular response to various challenges. Moreover, mounting evidence implicates ER stress in the regulation of cancer cell plasticity, including epithelial–mesenchymal plasticity, drug resistance phenotype, cancer stem cell phenotype, and vasculogenic mimicry phenotype plasticity. ER stress influences several malignant characteristics of tumor cells, including epithelial-to-mesenchymal transition (EMT), stem cell maintenance, angiogenic function, and tumor cell sensitivity to targeted therapy. The emerging links between ER stress and cancer cell plasticity that are implicated in tumor progression and chemoresistance are discussed in this review, which may aid in formulating strategies to target ER stress and cancer cell plasticity in anticancer treatments.